Expressive suppression is associated with state paranoia in psychosis: An experience sampling study on the association between adaptive and maladaptive emotion regulation strategies and paranoia. (20th February 2018) - Nittel, Clara Marie; Lincoln, Tania Marie; Lamster, Fabian; Leube, Dirk; Rief, Winfried; Kircher, Tilo; Mehl, Stephanie
Abstract : Objectives: Although emotional instability and problems in emotion regulation (ER) are known to be linked to the formation and maintenance of psychosis and paranoia, it remains unclear whether the use of specific ER strategies is associated with it. The first aim of the study was to explore the association between emotional instability and paranoia. The second and third aims were to investigate whether the use of maladaptive ER strategies leads to paranoia in patients with psychosis in daily life and whether the use of more adaptive ER strategies reduces paranoia. Design: A prospective momentary assessment study over the course of 6 days was performed. Method: Participants with psychosis ( n = 32) reported repeatedly over six consecutive days on the presence and instability of positive and negative emotions, their use of adaptive (reappraisal, acceptance, distraction, social sharing, reflection) and maladaptive ER strategies (rumination, expressive suppression) and momentary paranoia in their daily life. Results: Hierarchical linear regression analysis revealed that patients with psychosis who presented pronounced instability of negative emotions showed more severe levels of state paranoia. In addition, patients with psychosis who used expressive suppression when confronted with negative emotions at one point in time presented more pronounced levels of state paranoia at the following point in time. Conclusion: The results presented here suggest that both emotional instability and the use of expressive suppression might cause state paranoia and thus add to our understanding of causal mechanisms related to paranoia such as instability of negative emotions and the use of less adaptive ER strategies. Practitioner points: Maladaptive emotion regulation strategies and more pronounced instability of negative emotions are relevant to paranoia in patients with psychosis and should be a special focus of CBTp interventions. Future interventions designed for patients suffering from paranoia should promote coping with unstable negative emotions and replacing or reducing maladaptive emotion regulation strategies with adaptive ones.